Порядок примусового відчуження нерухомого майна з мотивів суспільної необхідності: цивільний аспект - Нівня, М. І.; Нивня, М. И.; Nivnja, M. (Одеса : Юрид. л-ра, 2014)
In the article there is investigated the existing order of compulsory acquisition of immovable property for the reasons of public necessity – namely, in terms of balance between public and private interests, are analyzed its disadvantages and identified the ways to balance as well as clarified the application of civil law approaches concerning improvement of the mentioned order.
Нівня М. І. Порядок примусового відчуження нерухомого майна з мотивів суспільної необхідності: цивільний аспект / М. І. Нівня // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 275-280.
Keywords: примусове відчуження; примусовий викуп; приватна власність; нерухоме майно; суспільна необхідність; принудительное отчуждение; принудительный выкуп; частная собственность; недвижимое имущество; общественная необходимость; expropriation; compulsory acquisition; private property; real estate; public necessity